BENTUK AMAE DAN OMOIYARI DALAM CERPEN FUMINSHO - Yuliani Rahmah (KIRYOKU, 2018)
(Amae and Omoiyari’s form in Fuminsho's Short story) This article describes the embodiment of bushido values in a literary work. The value discussed is one of the Bushido element called Jin (means compassion) especially the form of amae and omoiyari. With literature research method,this article explain amae and omoiyari’s attitude which describes in a Japanese short story entitled Fuminsho. As a result it is known that despite the genre of science fiction, the short story of fuminsho contains amae and omoiyari which is shown by the relationship between the role of main characters and the other characters in the short story.Keywords : Short-story; Amae ; Omoiyari